Autograph letter from A. W. Thayer to Fiske - Thayer, Alexander Wheelock, 1817-1897:::Creator::::::::::::; Fiske, Daniel Willard, 1831-1904:::Contributor:::::::::::: (2021)
Autograph letter signed from Alexander Wheelock Thayer to Daniel Willard Fiske, [June 4], 1863, written from Trieste, Italy.